Crystal structure of 2-(pyridin-2-ylamino)pyridinium chloride dibenzyldichlorostannane, [C10H10N3]Cl, C14H14Cl2Sn - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
doi.org/10.1515/ncrs-2020-0375